Intrinsic Rewards and Employee's Performance With the Mediating Mechanism of Employee's Motivation - Manzoor, Faiza; Wei, Longbao; Asif, Muhammad (Frontiers in Psychology, 2021)
The prime goal of this study is to analyse the impact of intrinsic rewards on employee’s performance. It also focuses on the role of employee's motivation as an intervening factor. To achieve this objective data has been collected through the questionnaire method from small and medium enterprises of Pakistan. A total of 400 questionnaires were distributed to the target population, and 300 were received. To test the hypotheses the confirmatory factor analysis and structural equation modeling have been used. The main results of the study have shown a positive and significant impact of intrinsic rewards has on employee’s performance. Specifically, the study reveals that an employee’s motivation significantly mediates the association between intrinsic rewards and employee’s performance. In the lights of the findings, implications are outlined.